Advanced Extra Functionality CMOS‐based Devices. Issue 1 (January 2014) - Cristiano, Fuccio; Pichler, Peter; Tavernier, Clément; Windl, Wolfgang; Cristiano, Fuccio; Pichler, Peter; Tavernier, Clément; Windl, Wolfgang
Abstract This volume contains the proceedings of the E‐MRS 2013 symposium K, entitled "Physics and Technology of Advanced Extra Functionality CMOS‐based Devices" that was held from May 27th to May 31st 2013 in Strasbourg, France. In total, 93 papers were presented, including 13 invited presentations, 51 contributed oral presentations and 29 poster presentations. Our symposium provided an open forum for the presentation of original experimental and theoretical studies that contribute to the physical understanding of phenomena related to new materials and processes for devices that add extra functionality to conventional CMOS backbone processes. Going from core CMOS technology to CMOS derivatives implies a change of paradigm in R & D. While core CMOS technology aims at improved performance, particularly switching speed, it is mandatory for CMOS derivatives to find a trade‐off between the traditional view of device 'performance' (switching speed, ...) and increasingly critical low power consumption requirements (calling for improved control of leakage currents, standby power consumption, dark currents…). The high‐quality symposium contributions and the inspiring discussions in the various sessions all contributed to the symposium success, particularly thanks to the invited speakers who provided excellent reviews of their recent works and of the state‐of‐the‐art in their respective fields. The exciting opportunities and challenges associated to some specific More‐than‐Moore applications, such as CMOS imagers and healthcare applications were presented in the opening session by François Roy from STMicroelectronics and Sywert Brongers‐ma from Holst Centre/IMEC. Throughout the symposium, reviews of the main challenges related to most of the building blocks of advanced CMOS‐based devices were given in terms of both fundamental material studies and/or technology optimisation. These included substrate engineering (Eugene Fitzgerald, MIT), source/drain doping (Benjamin Colombeau, Applied Materials), dopant diffusion (Hartmut Bracht, Univ. Münster), source/drain silicide fabrication (Dominique Mangelinck, IM2NP‐CNRS) and high‐k gate stacks (Ramamurthy Ramprasad, Univ. of Connecticut). Physical modelling and simulation issues (from ab‐initio to continuum TCAD) were discussed during three dedicated sessions brightly introduced by Matthias Posselt from HZDR (solid phase recrystallization), Andreas Schenk from ETH Zurich (leakage current modelling) and Christoph Zechner from Synopsys (process technology simulations). Finally, recent advances in the field of 3D dopant/carrier characterisation were reported by Wilfried Vandervorst from IMEC, while the use of electrical characterisation to investigate the impact of source/drain defects on leakage currents and advanced MOSFET performances were discussed by Ray Duffy from Tyndall and Mireille Mouis from IMEP‐LAHC‐CNRS. These proceedings contain a selection of 48 manuscripts organised in 5 sections: – Doping and Thermal Processing: Basic Studies and Process Optimization – More‐than‐Moore and Advanced CMOS Devices – Atomistic Modelling and Continuum Simulations – Physical and Electrical Characterization – Silicides and Germanides. We would like to acknowledge the E‐MRS Headquarters staff for its outstanding assistance in organising the symposium as well as Wiley‐VCH staff for helping in the publication of these proceedings. We also wish to thank all contributors and attendees for their active participation to the symposium and all colleagues who reviewed the submitted manuscripts, and contributed in many cases to the improvement of the quality of the published articles. We also wish to congratulate the winners of the best student awards (Fabio Isa from L‐NESS Milano and Ruggero Milazzo from CNR‐IMM‐MATIS Padova) as well as the winners of the best poster awards (Thomas Kreiliger from ETH Zurich and Spyridon Stathopoulos from NTUA University Athens). Finally, the symposium organisers are grateful for the sponsorship provided by several companies and institutions (Ion Beam Services, Semilab, STMicroelectronics, Synopsys, and the CNRS), as well as for the support of the EU commission through the European Project ATEMOX (Advanced Technology Modelling for Extra‐Functionality Devices) that gave rise to the proposal for the organisation of this symposium. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)